Repurposing of Nitroxoline as an Alternative Primary Amoebic Meningoencephalitis Treatment - Javier Chao-Pellicer; Iñigo Arberas-Jiménez; Frieder Fuchs; Ines Sifaoui; José E. Piñero; Jacob Lorenzo-Morales; Patrick Scheid (MDPI AG, 2023)
Among the pathogenic free-living amoebae (FLA), Naegleria fowleri is the etiological agent of a fatal disease known as primary amoebic meningoencephalitis (PAM). Once infection begins, the lesions generated in the central nervous system (CNS) result in the onset of symptoms leading to death in a short period of time. Currently, there is no standardized treatment against the infection, which, due to the high virulence of the parasite, results in a high case fatality rate (>97%). Therefore, it is essential to search for new therapeutic sources that can generate a rapid elimination of the parasite. In recent years, there have already been several successful examples of drug repurposing, such as Nitroxoline, for which, in addition to its known bioactive properties, anti-Balamuthia activity has recently been described. Following this approach, the anti-Naegleria activity of Nitroxoline was tested. Nitroxoline displayed low micromolar activity against two different strains of N. fowleri trophozoites (IC50 values of 1.63 ± 0.37 µM and 1.17 ± 0.21 µM) and against cyst stages (IC50 of 1.26 ± 0.42 μM). The potent anti-parasitic activity compared to the toxicity produced (selectivity index of 3.78 and 5.25, respectively) in murine macrophages and human cell lines (reported in previous studies), together with the induction of programmed cell death (PCD)-related events in N. fowleri make Nitroxoline a great candidate for an alternative PAM treatment.